Tren Topik Penelitian Jurnal Terakreditasi Peringkat Sinta 2 Bidang Ilmu Perpustakaan Dan Informasi Di Indonesia Periode 2013-2019 (Analisis Subjek Menggunakan Pendekatan Bibliometrik Co-Word) - Dwiyantoro Dwiyantoro (Perpustakaan Nasional, 2020)
This study aims to determine trends in research in the Sinta 2 accredited journal in the field of library and information science in Indonesia for the period 2013-2019. This research uses the bibliometric method using shared words. The number of samples to be analyzed were 400 journal articles from 4 journal editors, namely the BACA journal, the BIP journal, the Khizanah Al Hikmah Journal and JKIP journal for the 2013-2019 period. Conducting keyword groupings using subject analysis, after grouping based on the same keywords using the Jaccard index then analyzing using subject analysis based on the hawkins taxonomy. The results of this study indicate that research trends in accreditation journals in 2 fields of library and information science in the period 2013-2019 tend to be in 3 main taxonomies including Library and Library Services (LIS), Information Professionals, and Information Science Research (ISR). The conclusion of this study is that research trends are more inclined to Libraries and Library Services (LIS), The Professional Information, and Information Science Research (ISR). In the future, all researchers are expected to study other topics so that library development and information science are evenly distributed.